SCIENTIFIC PEDAGOGICAL FUNDAMENTALS OF INDIVIDUALIZATION IN EDUCATION OF FUTURE TEACHERS OF PHYSICAL CULTURE (Academicia Globe: Inderscience Research, 2022)
In the article, the essence of scientific pedagogical principles of individualization of physical culture of students in the educational process is studied. Individualization is the essence of students ' physical education and sports activities that have a major impact, it consists of physical exercises that maintain health for the organization of the circle.